2005
DOI: 10.4319/lom.2005.3.174
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of stream nutrient uptake from nutrient addition experiments

Abstract: Nutrient uptake in streams is often quantified by determining nutrient uptake length. However, current methods for measuring nutrient uptake length are often impractical, expensive, or demonstrably incorrect. We have developed a new method to estimate ambient nutrient uptake lengths using field experiments involving several levels of nutrient addition. Data analysis involves plotting nutrient addition uptake lengths versus added concentration and extrapolating to the negative ambient concentration. This method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
125
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 26 publications
3
125
1
3
Order By: Relevance
“…Second, there are very few measurements of Monod coefficients for nutrient uptake by heterotrophic microbes. The technique developed by PAYN et al (2005) may be useful for such measurements. Third, we found no actual measurements of dead microbial tissue in decaying leaves in streams.…”
Section: Is There a Net Retention Or A Net Mineralization Of Nutrientmentioning
confidence: 99%
“…Second, there are very few measurements of Monod coefficients for nutrient uptake by heterotrophic microbes. The technique developed by PAYN et al (2005) may be useful for such measurements. Third, we found no actual measurements of dead microbial tissue in decaying leaves in streams.…”
Section: Is There a Net Retention Or A Net Mineralization Of Nutrientmentioning
confidence: 99%
“…Uptake lengths measured with short-term nutrient addition techniques (S w9 ) overestimate the actual uptake length (S w ) at ambient conditions (Mulholland et al 1990, 2002, Earl et al 2006. Ambient U t estimates from S w9 will underestimate the actual ambient U t as measured with stable isotope tracers , and multiple additions are required to extrapolate ambient S w and U t (Payn et al 2005. We anchored ambient uptake parameters with published 15 N studies and reported U t of NO 3 2 at the elevated addition concentrations experienced during the addition.…”
Section: Responses To Acute and Chronic N Increasesmentioning
confidence: 99%
“…Dodds et al (2002) reported a K s of 64 mg NH 4 + -N/L for a prairie reach of Kings Creek, whereas Kemp and Dodds (2002b) projected whole-stream K s of 12.3 mg/L for NO 3 2 and 6.7 mg/L and NH 4 + based on uptake kinetics of different substratum types within the stream. Payn et al (2005) reported K s in forested streams of 6 mg NH 4 + -N/L for Ball Creek, North Carolina (USA), and 14 mg NH 4 + -N/L for Walker Branch, Tennessee (USA). In both streams, reported K s was higher than ambient NH 4 + concentrations (3.0 and 2.7 mg/L, respectively), results suggesting these streams are N limited.…”
mentioning
confidence: 99%
“…The principal reason for this constraint is methodological, specifically a strong reliance on two methods: 15 N isotopic tracer addition (Hall et al 1998;Dodds et al 2000;Peterson et al 2001) and nutrient enrichment (Mulholland et al 2002;Payn et al 2005), both of which create logistical and financial limitations when applied to larger rivers. Isotopic enrichment, which is desirable because it retains ambient concentrations and yields pathway-specific removal information, is particularly impractical in large rivers because of the costs of isotopically labeled solutes.…”
mentioning
confidence: 99%
“…Isotopic enrichment, which is desirable because it retains ambient concentrations and yields pathway-specific removal information, is particularly impractical in large rivers because of the costs of isotopically labeled solutes. Unlabeled nutrient enrichment additions, despite not discriminating removal pathways, are more feasible at higher flows and longer residence times (Tank et al 2008), but may enhance removal rates (Mulholland et al 2002), requiring repeated dosing to varying plateau concentrations to backextrapolate removal at ambient conditions (Payn et al 2005). Pulse injection methods (Covino et al 2010) to estimate both ambient concentration removal rates and removal kinetics with increased concentration obviate constraints of repeated plateau additions, but retain substantial logistical constraints in large rivers, and in river networks.…”
mentioning
confidence: 99%